Role of annexin 1 gene expression in mouse craniofacial bone development - Damazo, Amilcar Sabino; Moradi-Bidhendi, Niloufar; Oliani, Sonia Maria [UNESP]; Flower, Roderick John (Wiley, 2007)
BACKGROUND: Annexin 1 is a 37-kDa protein that has complex intra- and extracellular effects. To discover whether the absence of this protein alters bone development, we monitored this event in the annexin-A1 null mice in comparison with littermate wild-type controls. METHODS: Radiographic and densitometry methods were used for the assessment of bone in annexin-A1 null mice at a gross level. We used whole-skeleton staining, histological analysis, and Western blotting techniques to monitor changes at the tissue and cellular levels. RESULTS: There were no gross differences in the appendicular skeleton between the genotypes, but an anomalous development of the skull was observed in the annexin-A1 null mice. This was characterized in the newborn annexin-A1 null animals by a delayed intramembranous ossification of the skull, incomplete fusion of the interfrontal suture and palatine bone, and the presence of an abnormal suture structure. The annexin-A1 gene was shown to be active in osteocytes during this phase and COX-2 was abundantly expressed in cartilage and bone taken from annexin-A1 null mice. CONCLUSIONS: Expression of the annexin-A1 gene is important for the normal development of the skull in mice, possibly through the regulation of osteoblast differentiation and a secondary effect on the expression of components of the cPLA2-COX-2 system. © 2007 Wiley-Liss, Inc.
Keywords: Annexin 1; Bone; Cyclooxygenase-2; Cytosolic phospholipase A2; Osteoblast; annexin; annexin 1; cyclooxygenase 2; phospholipase A2; protein; unclassified drug; adolescent; animal tissue; annexin a1 gene; bone density; controlled study; craniofacial development; female; gene; gene activation; histology; immunohistochemistry; male; mouse; newborn; nonhuman; ossification; osteocyte; priority journal; protein expression; skull suture; Western blotting; Animals; Animals, Newborn; Annexin A1; Bone and Bones; Bone Density; Bone Development; Craniofacial Abnormalities; Cyclooxygenase 2; Female; Gene Expression; Homozygote; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Osteogenesis; Phospholipases A; Animalia; Mus